Pornografia de vingança e juventude: perspectivas teóricas e o estímulo ao debate com vídeos informativos - Rocha, Yara Cristina da (2021)
This research proposes to analyze, with the help of the targeted bibliography, the elements that circumvent the revenge pornography event, particularly focused on vexatious, undue exposure and moral lynching against women, as well as the components that fuel the search and consumption of videos on the topic on the basis of YouTube. Highlighting the path built by technological revolutions, until the virtual boom that took over the daily lives of individuals, some weaknesses that are transposed between the boundaries of the real and the virtual will be demonstrated, combining characteristics of interpersonal relationships in virtual planes. In addition to the focus on comparing videos from the virtual base, the research focuses on points that also seeks to investigate the impact of revenge pornography on the relationships of young people and adolescents, especially those who have some connection with the school environment. Despite configuring itself as a fairly impartial event between genders and age groups, the text intends to indicate how the phenomenon exposes its greater scope among young women, with specific mechanisms for acting and penalizing victims. Some notes will be addressed about the general concept of violence and the interweaving it makes with the school, with the culture that emanates from this environment and that establishes links with the main theme, in addition to the support of gender studies that support the construction of the proposed perspective in the discussion. The research relies on the theoretical contributions of Critical Theory, which discusses some of the effects of technology on society, historical surveys on the history of computing, internet and the expansion of use in peoples daily lives, education studies aimed at analyzing violence and school culture, in addition to the current processes that seek to articulate the new digital scenario to the curriculum, and highlights of feminist literature and gender studies, which aim to denounce discriminatory elements and promote the debate against the violence and paradigms wich are socially reproduced.